Theoretical platform for designing virtual excursions and their scenarios - Kuna, Peter; Hašková, Alena; Borza, Ľuboš (International Journal of Innovative Research and Scientific Studies, 2025)
Virtual schooling can be seen as a phenomenon that is going to contribute significantly to the development of all areas of human society. The professional interest of the authors of the paper is focused on the use of virtual reality in education in general, and specifically on the issue of replacing field excursions with their virtual alternatives within the framework of secondary vocational education and training. In the paper, they present a literary study whose aim is to offer a general theoretical platform for the development of these kinds of didactic means or teaching aids. The study deals with defining and distinguishing the content of the basic terms associated with the creation of a virtual environment, namely the terms of virtual reality and virtual world, along with the pedagogical aspects of both field trips and virtual excursions, as well as the factors influencing the creation of virtual excursions. To illustrate the elaborated study, the authors present a scenario of a virtual excursion created by them (Virtual excursion of a robotic line to process metal products) which is available at the link https://www.youtube.com/watch?v=yG-0d8gZXFw&t=187s and shows how engineering education and the preparation of the future workforce can be supported by these kinds of teaching means.